2(2x+1)-3(8-3x)=

Simple and best practice solution for 2(2x+1)-3(8-3x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+1)-3(8-3x)= equation:


Simplifying
2(2x + 1) + -3(8 + -3x) = 0

Reorder the terms:
2(1 + 2x) + -3(8 + -3x) = 0
(1 * 2 + 2x * 2) + -3(8 + -3x) = 0
(2 + 4x) + -3(8 + -3x) = 0
2 + 4x + (8 * -3 + -3x * -3) = 0
2 + 4x + (-24 + 9x) = 0

Reorder the terms:
2 + -24 + 4x + 9x = 0

Combine like terms: 2 + -24 = -22
-22 + 4x + 9x = 0

Combine like terms: 4x + 9x = 13x
-22 + 13x = 0

Solving
-22 + 13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 13x = 0 + 22

Combine like terms: -22 + 22 = 0
0 + 13x = 0 + 22
13x = 0 + 22

Combine like terms: 0 + 22 = 22
13x = 22

Divide each side by '13'.
x = 1.692307692

Simplifying
x = 1.692307692

See similar equations:

| n^2-8=0 | | 5x+6/8=7 | | 3x-6/2=30 | | 3x-4=+2-5x | | w=6/9 | | -2[3x+4]-x+6=-5x-2[x+1]+5 | | 2x-5/3=6 | | 0.25[3-x]=0.375 | | 6(4a-7)= | | 3(4e+9)=111 | | 7(3u-2)=28 | | 2(2x+1)-3(2-3x)= | | 6(2a+1)-2(2-3a)= | | 9x-11=6x+30 | | 2[3x+4]-[x-8]=3[4x+2]-7x+10 | | 15=3(2a-3) | | x=41/7 | | 6=9w | | 6x=14x-56 | | 7[4x+9]-13=-87 | | D^2+7b+10=0 | | 0.20x-0.08[x-10]=24.80 | | 5x-5(4)=2(4)+7 | | 5/13d8d/585/13d | | 6y-8=2y+8 | | 78=-9x-3[-56+12x] | | 3[2x+7]-3x=18 | | (6a-4)/7=8 | | -3j+15=-117 | | 1.95[6.2-3x]-4.81=-18.46 | | 2(a-2)=-a-1/a-4 | | 8x=x-12 |

Equations solver categories